Tracking and Predicting the German Economy: ifo vs. PMI - Robert Lehmann; Magnus Reif (Center for Economic Studies and ifo Institute (CESifo), 2020)
This analysis investigates the predictive power of the most important leading indicators for the German economy, which are provided by the ifo Institute and IHS Markit. We conduct an out-of-sample, real-time forecast experiment for growth of gross domestic product and growth of gross value added in both the manufacturing and the service sector. We find that both survey providers produce valuable leading indicators to predict the current quarter of German GDP growth. Regarding forecasts for the next quarter, the ifo indicators are slightly better than the IHS Markit headline index. For the manufacturing sector, series provided by ifo are clearly superior to those of IHS Markit. For the service sector, the ifo indicators produce better nowcasts, whereas the indicators by IHS are more valuable for one-quarter-ahead predictions.
Keywords: E17; E27; E37; 330; forecasting nowcasting; survey data; ifo Business Climate; PMI